Hungarian Travellers’ Writings on Spanish Women, 1808-1911 - Kéri, Katalin (Historiografías, 2024)
AbstractAlthough Spain and Hungary are geographycally distant, the transport revolution taken place in the XIXth century provided travels between both countries with fruituful opportunities. In this study we shall examine narratives of travellers, who set foot in the Iberian Peninsula in those years. These took the form of printed works in Hungarian language, particularly travel guides and newspaper articles, offering detailed descriptions on a long list of aspects such as landscapes, architecture, settlements, history, politics, music, lifestyle, dress, appearance, and gastronomy. It is about an information with interesting details concerning coeval society, and specially contemporary women – an aspect which is highlighted in the article –, based upon clichés and stereotypes about the national character or so-called Spanish temperament. Stemmed from romantic canon, in women’s case, they emphsised qualities such as beauty and exotism, and emotions such as the passionate character. In women travellers’ specific account, is to also worth adding that most of them did not know the Spanish language.KeywordsTravel guides to Spain, women’s history, 19th century, Hungarian sources, romantic stereotypes